Navigating Society 5.0: Unraveling the Dynamics of a People-Centric Super-Smart Society - Abdullah, Assyari; Jayus, Jayus; Yazid, Yasril; Sumaiyah, Sumaiyah; Khairi, Akmal; Edison, Edison; Astuti, Dwi Sutri; Mutasir, Mutasir (Universitas Muhammadiyah Ponorogo, 2024)
Society 5.0: A People-centric Super-smart Society